Emergy efficiency analysis of sugarcane as a raw material for ethanol production - da Vitória, Edney; Rodrigues, Joice (Revista Ciência Agronômica, 2016)
In recent years, the expansion of sugarcane cultivation in Brazil and its growing importance in the Brazilian economy have been driven by a sharp increase in fuel alcohol production. This increase in fuel alcohol production was accompanied by increasing interest regarding the impacts of fuel crops in Brazil. In this study, regions of sugarcane expansion into deforested areas in the Atlantic Forest were studied by applying the emergy theory and indices. Environmental and economic inputs and the sustainability of the sugarcane production system were evaluated with the emergy method. The transformity (TR) was equal to 1.78E+11 seJ kg-1, the yield rate (EYR) was equal to 1.30, the investment rate was equal to 3.29, the environmental load rate was equal to 4.33, the renewability rate was equal to 18.77, and the exchange rate was equal to 1.09. The emergy indices of corn, cassava, wheat, and sugarcane (as raw materials for ethanol production) were used. In Brazil, sugarcane production for ethanol production was more emergetically sustainable based on the analysed emergy indices.